Apply the theorem in Sec. 22 to verify that each of these functions is entire: (a) f (z) = 3x
(a) f (z) = 3x + y + i(3y − x);
(b) f (z) = sin x cosh y + i cos x sinh y;
(c) f (z) = e−y sin x − ie−y cos x;
(d) f (z) = (z2 − 2)e−x e−iy.
This problem has been solved!
Do you need an answer to a question different from the above? Ask your question!
Step by Step Answer:
Create a free account to access the answer
Cannot find your solution?
Post a FREE question now and get an answer within minutes. * Average response time.
Question Posted: June 01, 2016 01:38:46